Economic analysis of gas heat pump in different building applications:A case study in Shanghai - Lijun Wang; Zhiguang Chen; Chaokui Qin; Yuanyuan Gu (Case Studies in Thermal Engineering, 2022)
The application of gas engine driven heat pump (GHP) system can improve the peak valley difference of power and gas system and promote the low-carbon utilization of energy system. The energy consumption of GHP system in different types of buildings and especially the coefficient of performance (COP) under partial load rate needs more analysis. In this paper, according to the local meteorological parameters in Shanghai, the COP operation curve of GHP and electric driven heat pump (EHP) units under partial load rate was analyzed. Combined with the load calculation, the annual energy consumption of GHP and EHP units in different types of buildings, and the influence of energy price on economy of GHP system were analyzed. For office buildings and catering buildings, the energy consumption and operating costs of GHP system were slightly lower than those of EHP system, while for hotel buildings, the annual operating costs of GHP were lower than those of EHP only when the winter gas price was 2.39 yuan/m3 and the summer gas price was 2.19 yuan/m3. Therefore, in order to promote the market competitiveness of gas air conditioning, it is necessary to further refine the gas price or charge standard.